Analysis of Cementum Layers in Archaeological Material - Michaela Huffman; Daniel Antoine (Dental Anthropology Association, 2010)
The aim of this study was to assess the utility of cementum layers for estimating age at death of remains from an archaeological site. Variability in cementum layer counts due to interobserver error and variation among dental regions were analyzed. Interobserver error was later incorporated into age ranges based on counts of cementum layers and compared with age estimates derived from the skeleton. The layers were counted, using 9 teeth from 3 individuals, and the eruption age of the tooth was summed with the average layer count to achieve an estimated age. The research indicates that the assessment of archaeological dental cementum layers has a relatively high interobserver error. The cementum layer aging method resulted in large age ranges and did not correspond with age ranges from skeletal techniques. Chemical diagenetic processes can affect the observation and count of cementum layers by obscuring bands and/or creating additional bands. The variables that affected observability of cementum layers were: high interobserver error, discrepancy of readability of root regions, and large age ranges using the cementum layer technique that exceeded age ranges derived from other, skeletal methods.